2022
DOI: 10.3233/jad-220295
|View full text |Cite
|
Sign up to set email alerts
|

The Tryptophan Catabolite or Kynurenine Pathway in Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Alzheimer’s disease (AD), which is characterized by progressive brain dysfunction and memory loss, is one of the most significant global health concerns for older adults. Neuroinflammation and increased oxidative stress contribute to the pathophysiology of AD, thereby presumably inducing tryptophan (TRP) degradation through the TRP catabolite (TRYCAT) pathway. Objective: To delineate the activity of the TRYCAT pathway along with levels of TRP and tryptophan catabolites (TRYCATs) in AD patients. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…The effect size was described as large, moderate, and small based on the SMD values of 0.80, 0.5, and 0.20, respectively (Cohen 1988). In accordance with prior meta-analyses (Almulla, Vasupanrajit et al 2022, Vasupanrajit, Jirakran et al 2022), heterogeneity was determined by calculating tau-squared statistics, although we also show the Q and I 2 metrics. To identify the causes of heterogeneity in the present meta-analysis, a meta-regression was conducted.…”
Section: Methodsmentioning
confidence: 60%
See 3 more Smart Citations
“…The effect size was described as large, moderate, and small based on the SMD values of 0.80, 0.5, and 0.20, respectively (Cohen 1988). In accordance with prior meta-analyses (Almulla, Vasupanrajit et al 2022, Vasupanrajit, Jirakran et al 2022), heterogeneity was determined by calculating tau-squared statistics, although we also show the Q and I 2 metrics. To identify the causes of heterogeneity in the present meta-analysis, a meta-regression was conducted.…”
Section: Methodsmentioning
confidence: 60%
“…Nonetheless, our negative results concerning TRYCAT and IDO levels do not support the theory that activation of IDO/TDO is involved in MDD/BD (Maes 2015). While the TRYCAT pathway is activated during severe IRS responses, such as acute COVID-19 infection (Almulla, Supasitthumrong et al 2022) and IFN-α therapy (Bonaccorso, Marino et al 2002), no such changes may be observed in conditions of mild chronic inflammation, such as MDD/BD (this study) and Alzheimer’s disease (Almulla, Supasitthumrong et al 2022). Since plasma/serum TRP concentrations are around 50 μmol/L while KYN concentrations are around 3 μmol/L, TRP is abundantly available as a substrate for KYN formation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The last author (MM) was consulted in the case of controversial results. The last author slightly adjusted the "immune confounder scale (ICS)" published previously [36][37][38] to estimate the methodological quality of TRY CAT studies. This ICS and the related repoint checklist are shown in Additional file 1: Table S2.…”
Section: Screening and Data Extractionmentioning
confidence: 99%